Caminhos de uma transplantação religiosa: Ananda Marga e a formação de instrutores de yoga - Stockler, Leonardo (2020)
This work intends to investigate the transplantation of the indian religious organization Ananda Marga to Brazil taking as a sample the Tantra Yoga instructor training course offered by the organization, held throughout 2018 in the city of São Paulo. Our interest is to verify the importance and the meaning of a course of formation of instructors for the process of transplantation -to what extent it can help and inaugurate new aspects of this process, taking the spiritual message of the organization to non-religious spaces and outside the institution. Religious transplantation is a phenomenon common to the dynamics of religions in the globalized world, and the choice to focus our analysis on a training course meets the idea of verifying its aspects within a complex empirical sampling in which various trends intersect, so that we can outline the particularities of this process and its effects on the pluralization at the intersection of the religious field with the yoga market in Brazil. Thus, we tell a part of the history of the organization, itsinternationalization around the world, and its arrival in the country. In addition, the work aims to analyze the proposals of the association's founder, Prabhat Ranjan Sarkar, through which we can understand Yoga as an activity integrated to a system of universalist political and spiritual renewal in which issues concerning the formation of human subjects and the transformation of society are involved